Doing research in social work and social care: the journey from student to practitioner researcher - Catherine Flynn; Fiona McDermott (London: Sage, 2016)
This book guides students to becoming researchers by detailing the concepts of research and gathering data, to writing it all up and sharing knowledge to students.
Keywords: Social Service; Social sciences